THE CHEMISTRY OF SPRING WATERS AND FUMAROLIC GASES ENCIRCLING SANTA MARíA VOLCANO, GUATEMALA: INSIGHTS INTO REGIONAL HYDROTHERMAL ACTIVITY AND IMPLICATIONS FOR VOLCANO MONITORING - Walker J.A.; Templeton S.; Cameron B.I. (My University, 2006)
Springs encircling Santa María volcano in Guatemala generally contain bicarbonate waters. Bicarbonate waters southwest of the persistently active Santiaguito lava dome are characterized by high Mg/Ca. Other springs contain acid sulfate or chloride waters. Most acid sulfate and chloride waters are spatially confi ned to springs, wells, and streams of the Zunil and Zunil-II (Sulfur Mountain) geothermal fi elds on the fl anks of the Cerro Quemado dome complex, 5 km to the east-northeast of Santa María. Some acid sulfate waters have unusually high S/Cl ratios (20-70). Chloride waters are dilute versions of typical geothermal brines. The δ13C ratios of all waters fall in a very narrow range (-11.5‰ to -8.5‰). The nonreactive gas compositions from fumaroles encircling Santa María are typical of those sampled at other subduction zone volcanoes. Most fumarolic gases from Santa María have notably lighter δ13C ratios compared to gases sampled from elsewhere on the Central American volcanic front. The He and C isotopic values of fumarolic gas samples from the Santa María region indicate signifi cant mantle input. Estimated magmatic δ13C ratios for Zunil and Zunil-II, however, are lighter than accepted mantle values (-11‰ to -14‰). This is most likely caused by shallow crustal contamination. All of the spring waters from the Santa María region represent variable interactions between magmatic/ hydrothermal fl uids and meteoric waters. There is, however, only limited mixing between bicarbonate, acid sulfate, and chloride waters. Surface discharges of chloride waters are inhibited by high precipitation rates. The high S/Cl ratios of some of the acid sulfate waters from Zunil/Zunil-II refl ect extensive scrubbing by the underlying hydrothermal system. High Mg/Ca bicarbonate waters from springs south-southwest of the Santiaguito dome complex have experienced enhanced water-rock interaction, and their slightly heavier δ 13C ratios (-9.5‰ to -8‰) hint at a small distinction between magmatic δ13C at Zunil/Zunil-II and Santa María. This supports previous suggestions that the hydrothermal system beneath the Zunil area is independent of Santa María. Gas samples from Zunil/Zunil-II and Cerro Quemado, on the other hand, do share similar δ13C ratios, strengthening the notion that magmatism at the latter is propelling the hydrothermal system northeast of Santa María. Hence, monitoring of the springs and fumaroles at Zunil/Zunil-II could prove useful in forecasting of future activity at Cerro Quemado. © 2006 Geological Society of America.
Keywords: GUATEMALA; HYDROTHERMAL SYSTEM; SANTA MARíA; VOLCANIC GASES; VOLCANIC SPRINGS